Lack of the human choline transporter‐like protein SLC44A2 causes hearing impairment and a rare red blood phenotype. Issue 3 (25th January 2023) - Koehl, Bérengère; Vrignaud, Cédric; Mikdar, Mahmoud; Nair, Thankam S; Yang, Lucy; Landry, Seyve; Laiguillon, Guy; Giroux‐Lathuile, Claudine; Anselme‐Martin, Sophie; El Kenz, Hanane; Hermine, Olivier; Mohandas, Narla; et al.
Abstract: Blood phenotypes are defined by the presence or absence of specific blood group antigens at the red blood cell (RBC) surface, due to genetic polymorphisms among individuals. The recent development of genomic and proteomic approaches enabled the characterization of several enigmatic antigens. The choline transporter‐like protein CTL2 encoded by the SLC44A2 gene plays an important role in platelet aggregation and neutrophil activation. By investigating alloantibodies to a high‐prevalence antigen of unknown specificity, found in patients with a rare blood type, we showed that SLC44A2 is also expressed in RBCs and carries a new blood group system. Furthermore, we identified three siblings homozygous for a large deletion in SLC44A2, resulting in complete SLC44A2 deficiency. Interestingly, the first‐ever reported SLC44A2‐deficient individuals suffer from progressive hearing impairment, recurrent arterial aneurysms, and epilepsy. Furthermore, SLC44A2null individuals showed no significant platelet aggregation changes and do not suffer from any apparent hematological disorders. Overall, our findings confirm the function of SLC44A2 in hearing preservation and provide new insights into the possible role of this protein in maintaining cerebrovascular homeostasis. Synopsis: Homozygous deletion in the SLC44A2 gene was identified in three siblings with a rare blood phenotype. SLC44A2 was confirmed to be essential in the physiology of hearing in humans, but dispensable for erythropoiesis and platelet aggregation. SLC44A2, a choline transporter‐like protein (CTL2), underlies a novel human blood group system. A missense mutation in SLC44A2 encodes a new red cell antigen, RIF, and a large deletion is responsible for a null phenotype (VER‐). New anti‐SLC44A2 alloantibodies, anti‐RIF and anti‐VER, induce neutrophil adhesion to endothelial cells and could be involved in transfusion‐related acute lung injury (TRALI). SLC44A2null individuals suffer from hearing impairment and recurrent intracranial aneurysms, but are not associated with neither apparent erythroid nor platelet disorders. Abstract : Homozygous deletion in the SLC44A2 gene was identified in three siblings with a rare blood phenotype. SLC44A2 was confirmed to be essential in the physiology of hearing in humans, but dispensable for erythropoiesis and platelet aggregation.